Tantangan Komunikasi Antarbudaya Sekarang Dan Yang Akan Datang Di Indonesia - Farhaeni, Mutria (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2022)
This paper discusses the challenges of intercultural communication now and in the future in Indonesia. The method used is a qualitative approach based on the literature which aims to examine the challenges of intercultural communication now and in the future in Indonesia. From the results of the study then narrated in descriptive form. It can be concluded that the current and future challenges of intercultural communication in Indonesia include globalization, international conflict and security, global competition for natural resources, global healthcare issues, and population change. It is hoped that the government and society can prevent and deal with the challenges of intercultural communication now and in the future in Indonesia, including globalization, international conflict and security, world competition for natural resources, world health care problems, and population change. Keywords:  challenges, communication, intercultural, now, in the future